Pemikiran Pendidikan Islam Pada Era Kontemporer - Sain Hanafy (LPPM IAIN Sorong, 2018)
This paper discusses the development of contemporary Islamic education by describing the thoughts of Abdurrahman Mas'ud, Hasan Langgulung, and Abdul Munir Mulkhan. Abdurrahman Mas'ud offers the humanistic and religious format of nondikotomic education, which connects human beings with their God (Hablum Minallah) and between human and human (Hablum Minannas). The purpose of education according to him is to prepare life in the world and the hereafter. Hasan Langgulung offers an idea of the principles of Islamic education. According to him, education can be viewed from two points of view. First, from the perspective of society, that education is a process of cultural inheritance, from the old generation to the younger generation, so that the community can maintain its personality with the basis of Islamic values. Second, from individual perspective, education means the development effort of individual potentials to be actualized concretely so that the results can be beneficial to individuals and society. Langgulung educational thinking is based on the perspective of psychology, education is needed to meet and maintain the sustainability of human life. While Abdul Munir Mulkhan's educational thought is more influenced by a sociological perspective critically. In general, education only prioritizes aspects of intelligence (cognition) and skills (psychomotor), thus ignoring the aspects of personality (emotional). Therefore, he argues, spiritual reasoning is the solution to the philosophical problems of education because the personality or consciousness of manners will increase religiosity (spiritual intelligence) as the base of creative consciousness. According to Mulkhan, education is the right of human beings in maintaining humanitarian agreements so that in their life will realize the awareness of pluralism in the society